Cultural Practices and Lifestyle of the Momogun Rungus Tribe of the Bavanggazo Longhouse Community in Sabah, Malaysia: Ethnographic Notes (International Journal of Linguistics and Indigenous Culture, 2024)
This study investigates the cultural practices and lifestyle of the Momogun Rungus Tribe in Sabah, Malaysia, focusing on their communal living in the Bavanggazo Longhouse. Utilizing a micro-ethnographic approach, the research documents traditional practices, agricultural activities, rituals, and the linguistic and medicinal knowledge of the Rungus people. The Bavanggazo Longhouse, a significant cultural site, offers valuable insights into the tribe's historical and contemporary life. The findings reveal the critical role of traditional ceremonies, such as the Magahau festival, and the importance of the Rungus language and medicinal practices in maintaining cultural identity. Health challenges and the impact of modernization on cultural practices were also examined. This study highlights the necessity of preserving the Rungus cultural heritage amidst modernization pressures, contributing to a deeper understanding of Malaysia's cultural diversity and offering a resource for future preservation efforts. The comprehensive documentation aims to support cultural preservation initiatives and foster appreciation of the Rungus Tribe's rich heritage